Coadministration of the Three Antigenic Leishmania infantum Poly (A) Binding Proteins as a DNA Vaccine Induces Protection against Leishmania major Infection in BALB/c Mice. - Manuel Soto; Laura Corvo; Esther Garde; Laura Ramírez; Virginia Iniesta; Pedro Bonay; Carlos Gómez-Nieto; Víctor M González; M Elena Martín; Carlos Alonso; Eduardo A F Coelho; Aldina Barral; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Highly conserved intracellular proteins from Leishmania have been described as antigens in natural and experimental infected mammals. The present study aimed to evaluate the antigenicity and prophylactic properties of the Leishmania infantum Poly (A) binding proteins (LiPABPs). METHODOLOGY/PRINCIPAL FINDINGS:Three different members of the LiPABP family have been described. Recombinant tools based on these proteins were constructed: recombinant proteins and DNA vaccines. The three recombinant proteins were employed for coating ELISA plates. Sera from human and canine patients of visceral leishmaniasis and human patients of mucosal leishmaniasis recognized the three LiPABPs. In addition, the protective efficacy of a DNA vaccine based on the combination of the three Leishmania PABPs has been tested in a model of progressive murine leishmaniasis: BALB/c mice infected with Leishmania major. The induction of a Th1-like response against the LiPABP family by genetic vaccination was able to down-regulate the IL-10 predominant responses elicited by parasite LiPABPs after infection in this murine model. This modulation resulted in a partial protection against L. major infection. LiPABP vaccinated mice showed a reduction on the pathology that was accompanied by a decrease in parasite burdens, in antibody titers against Leishmania antigens and in the IL-4 and IL-10 parasite-specific mediated responses in comparison to control mice groups immunized with saline or with the non-recombinant plasmid. CONCLUSION/SIGNIFICANCE:The results presented here demonstrate for the first time the prophylactic properties of a new family of Leishmania antigenic intracellular proteins, the LiPABPs. The redirection of the immune response elicited against the LiPABP family (from IL-10 towards IFN-γ mediated responses) by genetic vaccination was able to induce a partial protection against the development of the disease in a highly susceptible murine model of leishmaniasis.